Effect of GRDP, Capital Expenditure, OSR, and HDI on Poverty in Kuantan Singingi Regency - Asnita Asnita; Harlen Harlen; Ando Fahda Aulia (JEJAK: Jurnal Ekonomi dan Kebijakan, 2023)
This research aimed to analyze the effect of Gross Regional Domestic Product (GRDP), Capital Expenditure, Own-Source Revenue (OSR), and the Human Development Index (HDI) on poverty in the Kuantan Singingi Regency. The data used was time series data from 2010 to 2021. The test was performed using multiple linear regression tools with OLS analysis techniques. The results showed that the GRDP and OSR significantly negatively affect poverty in Kuantan Singingi Regency. Poverty in Kuantan Singingi Regency will decrease as the GRDP and OSR increase. Meanwhile, Capital Expenditure has a significant effect on the poverty of Kuantan Singingi Regency. However, the HDI does not have a significant positive effect on the poverty of the Kuantan Singingi Regency.